Tren Publikasi Ilmiah dalam Kajian Digitalisasi Pelayanan Publik : Analisis Bibliometric Data Scopus - Jiwa Riwayanti; Bambang Suprianto (Jurnal Media Administrasi, 2025)
This study examines trends in scientific publications on digitalization from 2014 to 2024 published in Scopus-indexed journals worldwide. Data were collected from the Scopus database on October 6, 2024, at 21:56 WIB using the keywords "Digitalization" and "Public Services." A total of 593 documents were found in various categories, including titles, abstracts, and keywords. To analyze these documents, the authors employed the VOSviewer program (version 1.6.17), which enables the visualization of relationships in research data. The search analysis on document results was used to complete the data collection process, followed by detailed data analysis. The research data was analyzed through infographic mapping, which visualized research developments and document mapping on various aspects such as affiliations, countries, subject areas, and types of publications. This analysis revealed significant correlations among studies focused on the digitalization of public services. The findings show that research on the digitalization of public services from 2014 to 2024 has consistently grown year after year, with 593 published documents discussing the issue across different countries. The Russian Presidential Academy of National Economy and Public Administration emerged as the most active affiliation, publishing 14 documents on the topic. The Russian Federation ranked first in scientific publications, contributing 83 documents indexed by Scopus. In terms of subject areas, the study highlighted the growing importance of digitalization in enhancing public services globally. The VOSviewer analysis revealed strong connections among studies in this field, further emphasizing the rising global focus on digitalization in public administration and governance. These trends reflect the growing significance of digital tools and technologies in improving the efficiency and accessibility of public services worldwide, signaling an ongoing and expanding area of academic and policy interest.